An Overview of the Status and Conservation Initiatives of Red Panda Ailurus fulgens (Cuvier, 1825) in Nepal - Bista, Damber; Paudel, Rajiv (The Initiation, 2014)
The existing status of Red Panda Ailurus fulgens in Nepal is poorly known. Current work attempts to put the information on Red Panda status together from Nepal and the conservation initiatives taken so far in the country. Red Panda inhabits eastern Himalayan temperate broadleaved forest with bamboo in the understory with an altitudinal range preference of 2400-3900 m. The Red Panda population in Nepal is about 314 individuals. Although the majority of potential habitat i.e. 62% lies in community managed and national forest, a very few initiatives have been started for the research and conservation of this species outside the protected areas. The Red Panda is protected in Nepal. Forest fire, rotational grazing, slash and burn cultivation, timber and fire wood collection, predation by dogs, natural dying of ringal bamboo species, drought, landslide and lack of awareness are identified as the major conservation threats for Red Panda throughout its habitat within the country. DOI: http://dx.doi.org/10.3126/init.v5i0.10268 The Initiation 2013 Vol.5; 171-181